An Analysis of Batu Bara Malay Students’ Pronunciation in English Consonant Cluster and Word Stress - Dwi Handayani Silitonga; Erika Sinambela; Arsen Nahum Pasaribu (Institut Agama Islam Negeri Palopo, 2021)
Pronunciation has many great important roles in one speaking performance. The inappropriate pronounced words cause the negative impact of misunderstanding. Therefore, this study aims to find out how the pronunciation of Batu Bara Malay students, particularly the English consonant clusters and the word stress, and to identify the factors affecting Batu Bara Malay students’ difficulties in pronouncing English consonant clusters and the word stress. The qualitative method was applied in this study. There were 25 students of seventh-grade students of SMP Negeri 1 Datuk Tanah Datar as the study subjects who speak the Malay Language as their mother tongue. The data were collected by recording students’ voice and interviewing. The researchers applied the Miles and Huberman model to analyze the data. The results are Batu Bara Malay students’ ability to pronounce English consonant clusters around 29%. Most of the students inaccurately utter the English consonant cluster word at the final position. The students’ ability in pronouncing English word by correct word stress rules around 30%. As the students' achievement under 50%, it means their ability in pronouncing consonant cluster and word stress is very low. These problems are caused by the existence of the mother tongue intervening in their process of learning another language and the distinction between English characteristics and nature compared with Indonesia Language (similar to the Malay language), particularly consonant clusters. English has more types of consonant. Besides that, the lack of both knowledge and pronunciation exercises on how to pronounce English word accurately for beginner learners so the students are unable to pronounce English consonant clusters and emphasize appropriate word stress.